Self-resonant microlasers of colloidal quantum wells constructed by direct deep patterning - Gheshlaghi, Negar (2021)
Here, the first account of self-resonant fully colloidal μ-lasers made from colloidal quantum well (CQW) solution is reported. A deep patterning technique is developed to fabricate well-defined high aspect-ratio on-chip CQW resonators made of grating waveguides and in-plane reflectors. The fabricated waveguide-coupled laser, enabling tight optical confinement, assures in-plane lasing. CQWs of the patterned layers are closed-packed with sharp edges and residual-free lifted-off surfaces. Additionally, the method is successfully applied to various nanoparticles including colloidal quantum dots and metal nanoparticles. It is observed that the patterning process does not affect the nanocrystals (NCs) immobilized in the attained patterns and the different physical and chemical properties of the NCs remain pristine. Thanks to the deep patterning capability of the proposed method, patterns of NCs with subwavelength lateral feature sizes and micron-scale heights can possibly be fabricated in high aspect ratios.